1988
DOI: 10.1002/clc.4960110807
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial contractility and performance capacity after magnesium infusions in young healthy persons: A double‐blind, placebo‐controlled, cross‐over study

Abstract: Summary: To evaluate the effect of intravenous magnesium (Mg) treatment on the inotropic state of the heart and maximal work capacity, 9 healthy volunteers were entered in a double-blind, placebo-controlled, cross-over study. Separated by an interval of three weeks, the volunteers were tested twice, each time randomly allocated to receive either an intravenous injection of 10 mmol magnesium chloride dissolved in 100 ml isotonic sodium chloride or placebo of isotonic sodium chloride only. Before and after each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…It has been systematically shown that magnesium salt infusion lowers BP via a reduction of TPR despite a moderate increase in cardiac output [8,[26][27][28]. The latter is accomplished via increases in HR and coronary flow [27] or a direct myocardial effect [28][29], independent of changes in preload, afterload, heart rate, or flow [29].…”
Section: Changes In Smgmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been systematically shown that magnesium salt infusion lowers BP via a reduction of TPR despite a moderate increase in cardiac output [8,[26][27][28]. The latter is accomplished via increases in HR and coronary flow [27] or a direct myocardial effect [28][29], independent of changes in preload, afterload, heart rate, or flow [29].…”
Section: Changes In Smgmentioning
confidence: 99%
“…The latter is accomplished via increases in HR and coronary flow [27] or a direct myocardial effect [28][29], independent of changes in preload, afterload, heart rate, or flow [29]. These Mg-induced direct or indirect vasodilatory effects are dose dependent [27] and can be elicited at plasma concentrations as low as 1.38 mmol/L [28], while a concentration of 1.8 to 3.0 mmol/L has been suggested for treatment of eclamptic convulsions [27]. According to our data, the substantial intradialytic fall of BP seen with a HD solution containing Mg and Ca concentrations of 0.25 mmol/L and 1.25 mmol/L, respectively, was due to an unusual impairment of myocardial contractility not compensated by an increased TPR.…”
Section: Changes In Smgmentioning
confidence: 99%
See 1 more Smart Citation
“…In a preparation of isolated animal heart, Mg, because of its anticalcium properties, caused a dose-dependent negative inotropic effect. 19 Rasmussen et al observed a moderate positive inotropic effect after infusion of Mg into healthy volunteers, 20 which could have been related to the vascular effect of Mg in reducing systemic arterial 20 and pulmonary artery pressures through a decrease of vascular resistance. 18 In in vitro studies on isolated aorta, the absence of Mg potentiated the vasoconstrictive effect of angiotensin and acetylcholine, and hypermagnesemia induced the relaxation of smooth muscle.…”
Section: Cardiovascular Effectsmentioning
confidence: 99%
“…A slight fall in blood pressure and rise in heart rate may be seen and the ratepressure product is unaltered. The haemodynamic response is similar in normal subjects and untreated hypertensives (Mroczek et al, 1977;Nadler et al, 1987;Rasmussen et al, 1988b) and in men with coronary artery disease (Borschat et al, 1988). Nadler et al (1987) infused 25 mmol MgSO4 over 3 h in normal subjects and observed a mean fall of 10 mm Hg in systolic and diastolic blood pressure, a 22% increase in renal blood flow and a 60% increase in urinary excretion of 6-keto-PGF1a, the stable metabolite of prostacyclin.…”
Section: Introductionmentioning
confidence: 99%